An investigation of transformation inclusivity in the strategic planning of built environment organisation in South Africa - Mabovu, Lunga (Department of Construction Economics and Management, 2025)
The transformation progress has been very slow in terms of delivering employment equity in the built environment. It appears that built environment organisations lack effective strategic plans that promote transformation, fail to use succession planning to embrace transformation, indulge in non-transparent recruitment and promotion procedures that further hamper transformation, and are not held accountable for their lack of transformation. The purpose of this research is to investigate the effect of lack of transformation inclusivity in the built environment organisations in South Africa. Thereafter find ways to stimulate the transformation inclusion into strategic planning of organisations across various sectors of economy. A quantitative research approach was adopted to provide hard, factual data. Descriptive research was conducted through a literature review, and a web-based survey to investigate the lack of transformation inclusion in the strategic planning of organisations in the built environment professions in South Africa. This study used probability sampling technique and applied cluster sampling to select the sample. A total of 36 respondents were surveyed. The results revealed that none of the respondents agree that employment equity is included in the strategic planning of their organisation. There is lack of incorporation of succession plan in the strategic planning of built environment organisations. The results showed that transparency on recruitment and promotional procedures is not clearly established. The results showed that there is no conclusive evidence on the accountability for not meeting employment targets. The lack of structured change management process is perceived as the main barrier to transformation. The study illustrates the importance of establishing transformation by overcoming imbalances in the HR processes of the organisations by revealing prominent barriers to employment equity in the built environment organisations. This will help HR practitioners and organisation management to establish organisation HR policies that are in line with Department of Labour (DoL) employment equity targets.